Фулерени — антиокисні присадки до нафтопродуктів - Ковтун, Г.О.; Жила, Р.С.; Каменєва, Т.М.; Плужніков, В.О. (Видавничий дім "Академперіодика" НАН України, 2008)
It is shown that fullerenes (C60, tert-C4H9C60H, Sc@C82) are antioxidative additives to oil products (mineral and synthetic oils, fuel). Fullerene C60 breaks the oxidation chains of basic oil MAC-35 by interacting with alkyl and peroxyl radicals simultaneously (120 ºС).